해수 내 캐비테이션-침식 저항성에 미치는 스테인리스강의 Nb 첨가의 영향 - 최용원(Yong-Won Choi); 한민수(Min-Su Han); 김성종(Seong-Jong Kim) (Biuletyn Uniejowski, 2016)
Stainless steel is widely used in various industries due to its excellent anti-corrosion characteristics. However, if the stainless steel is exposed to high speed fluid flow and chloride ion in the marine environment, corrosion and cavitation damage occurred on the surface easily. Therefore, to prevent these problems, stabilzed stainless steel is applied to offshore and shipbuilding industries. In this study, stabilized stainless steel specimen was made by 19%Cr-9%Ni with different Nb contents (0.29%, 0.46% and 0.71%). And then, their cavitation characteristics were investigated. As a result, the characteristics of cavitation resistance of stainless steel could be improved by increasing Nb contents.